2001
DOI: 10.1063/1.1352079
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of ultrathin ZrO2(111) films on Ni(111) from first principles

Abstract: We have studied the ZrO 2 ͑111͒/Ni͑111͒ interface using the ultrasoft pseudopotential formalism within density functional theory. We find that ZrO 2 (111) adheres relatively strongly at the monolayer level but thicker ceramic films interact weakly with the Ni-substrate. We argue that the cohesion changes character from dominantly image charge interactions for thick ceramic films to more covalent for monolayer ZrO 2 (111) films. We provide an analysis of energetic, structural and electronic aspects of the ZrO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
77
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 72 publications
11
77
0
Order By: Relevance
“…In the simulations, the interlayer distances were set to be 0.197 nm for the O-terminated model and 0.276 nm for the Zrterminated model across the interface, which were energetically stable bond lengths for Ni-O and Ni-Zr, reported by Christensen and Carter using ab initio calculations. 5) As can be seen from Fig. 4(c) and (d), dark spots correspond to Ni, Zr and O columns in these imaging conditions.…”
Section: Atomic Structurementioning
confidence: 63%
See 2 more Smart Citations
“…In the simulations, the interlayer distances were set to be 0.197 nm for the O-terminated model and 0.276 nm for the Zrterminated model across the interface, which were energetically stable bond lengths for Ni-O and Ni-Zr, reported by Christensen and Carter using ab initio calculations. 5) As can be seen from Fig. 4(c) and (d), dark spots correspond to Ni, Zr and O columns in these imaging conditions.…”
Section: Atomic Structurementioning
confidence: 63%
“…It is possible that not only the atomic and electronic structures but also the interfacial energy is different between Ni/ZrO 2 (001) and Ni/ZrO 2 (111) interfaces. According to recent theoretical studies, there are differences in the interfacial energies, which gives the actual stability of the each interface, between Ni(001)/ZrO 2 (001) 9) and Ni(111)/ZrO 2 (111) 5) interfaces, although the interface plane of Ni is different from each other. Furthermore, Beltrán et al reported that both the Zr-terminated and the Oterminated interfaces are energetically favorable in the Ni(001)/ZrO 2 (001) interface, 9) while Christensen and Carter reported that the O-terminated interface is energetically favorable in the Ni(111)/ZrO 2 (111) interface, 5) which is consistent with our result.…”
Section: Electronic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…We find an equilibrium Ni-O distance of d Ni-O ϭ1.94 Å, which is in the range of distances obtained at the ZrO 2 /Ni(111) interface, 5 although in that case oxygen is one-or threefold coordinated. The Mulliken populations evidence that there is a net charge transfer from Ni to O.…”
Section: Resultsmentioning
confidence: 83%
“…By contrast, the LDOS of ZrO 2 show significant 4d occupation, which suggests that the O anions in zirconia are more like O − than O 2− , i.e., the oxygen atoms have a partially open 2p shell that permits covalent bonding at interfaces (15). YSZ/Ni superalloy interfaces were also modeled (18); the more covalent zirconia indeed formed stronger bonds to Ni (W sep ∼ 1 J∕m 2 ) than the ionic alumina. However, repulsions between the nearly filled 3d shell of the Ni atoms and the ZrO 2 O anions reduced the zirconia/nickel adhesive strength relative to the zirconia/alumina interface.…”
Section: Resultsmentioning
confidence: 99%